The Moderating Effect of Benevolence on the influence of Corporate Governance on Audit Quality - Sailendra Sailendra; Etty Murwaningsari; Sekar Mayangsari; Murtanto Murtanto (AIBPM Publisher, 2020)
In this study, we aim to examine the influence of corporate governance on the audit quality of financial report moderated by benevolence. The research data consisted of 320 observations from 80 public listed companies in the manufacturing industry from 2013-2016. The research model has been tested using a data pool, with statistics on Structural Equalization Modeling - Partial Least Square (SEM-PLS). The results of the study get empirical evidence that corporate governance has a positive effect on audit quality. While benevolence as an independent variable has a negative impact on audit quality, however, benevolence as a moderating variable strengthens the influence of corporate governance on audit quality. Likewise, SIZE as control variables have a positive effect on audit quality, but ROA no impact on audit quality and LEV have a negative impact on audit quality. The result of this study have implications for investors, company management and regulators, that good corporate governance is inseparable from the benevolence of management in managing the company as a way to improve audit quality, is something essential and needs attention from all parties.